STRUKTUR KOMUNITAS KEPITING UCA PADA ZONA AVICENNIA HUTAN MANGROVE DESA SUNGAI BATANG KECAMATAN AIR SUGIHAN KABUPATEN OGAN KOMERING ILIR - Dewi Rosanti (Universitas PGRI Palembang, 2011)
ABSTRACTThe study has been done about structure and composition of Uca mangrove crabs on Avicennia zone in Sungai Batang Village Ogan Komering Ilir Regency, on November 2009 – Januari 2010. The aims of the research were to find out the density, frequency, important value index and diversity index of crabs. This research used survey methods with the approach used purposive random sampling in 10 traps.According to the observation and researching in laboratory can be found 8 species of genera Uca crabs. There were eight groups of taxonomic categories which can be found in these study namely Uca longisignalis, Uca dussumierri, Uca forcipata, Uca pugnax, Uca flammula, Uca roseus, Uca triangularis and Uca manii. Diversity index of phytoplankton as medium categorie with the value 2,85.Key words : avicennia zone,Uca crabs, mangrove